Understanding urban travel behaviour by gender for efficient and equitable transport policies - Wei-Shiuen Ng; Ashley Acker (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2018)
Gender is one of the key socio-demographic variables that can influence travel behaviour, but it is often the least understood. Understanding travel behaviour by gender will help better design transport policies that are efficient and equitable. Due to the gendered division of work in households, women often have multiple tasks and activities. As a result, women are more likely to have shorter commute distances, to chain trips, to have more non-work related trips, to travel at off-peak hours, and to choose more flexible modes. This study examines travel behaviour by gender in eight different cities, across three different continents, focusing on transport mode, trip purpose, travel distance and departure time for Auckland, Dublin, Hanoi, Helsinki, Jakarta, Kuala Lumpur, Lisbon and Manila. The most common trends found in the cities are that women tend to travel shorter distances and prefer public transport and taxi services to cars more than men.
Keywords: 330; Verkehrsmittelwahl; Stadtverkehr; Öffentlicher Verkehr; Sicherheit; Geschlechterunterschiede